Spheroidization behavior of water-atomized 316 stainless steel powder by inductively-coupled thermal plasma. (December 2020) - Park, Jae-Young; Park, Ki Beom; Kang, Jang-Won; Kim, Hyung Giun; Hwang, Nong-Moon; Park, Hyung-Ki
Highlights: 316 stainless steel powder fabricated by water atomization were spheroidized using inductively-coupled thermal plasma. After plasma treatment, water-atomized powders having irregular morphologies were perfectly spheroidized. The Concentrations of oxygen and Cr in the powders were decreased after spheroidization. Abstract: In the additive manufacturing process, fine powders having spherical shape are used due to their high flowability and packing density. When powders are produced by the water atomization method, it is advantageous to prepare fine powders, but powders having irregular shape are prepared, which is not suitable for the AM process. Therefore, in this study, 316 stainless steel powder fabricated by water atomization method were spheroidized using inductively-coupled thermal plasma. The initial water atomized 316 stainless steel powders had an irregular shape; however after spheroidization, their morphology was changed to a perfect spherical shape, which results in the drastic improvement of flowability. Examining the composition changes after spheroidizing, it was confirmed that the concentrations of oxygen and Cr were decreased. The reason for the decrease in oxygen concentration was that the temperature in the plasma process is extremely high and the oxygen partial pressure in the plasma chamber is low. The decrease in Cr concentration was caused by the evaporation of Cr during the spheroidization process, and the vapor pressure and evaporation coefficient of Cr in 316 molten liquid were calculated to analyze the reason.